The use of QBO, ENSO, and NAO perturbations in the evaluation of GOME-2 MetOp A total ozone measurements - Eleftheratos, K.; Zerefos, C.S.; Balis, D.S.; Koukouli, M.-E.; Kapsomenakis, J.; Loyola, D.G.; Valks, P.; Coldewey-Egbers, M.; Lerot, C.; Frith, S.M.; Haslerud, A.S.; Isaksen, I.S.A.; et al. (2019)
In this work we present evidence that quasi-cyclical perturbations in total ozone (quasi-biennial oscillation - QBO, El Niño-Southern Oscillation - ENSO, and North Atlantic Oscillation - NAO) can be used as independent proxies in evaluating Global Ozone Monitoring Experiment (GOME) 2 aboard MetOp A (GOME-2A) satellite total ozone data, using ground-based (GB) measurements, other satellite data, and chemical transport model calculations. The analysis is performed in the frame of the validation strategy on longer time scales within the European Organisation for the Exploitation of Meteorological Satellites (EUMETSAT) Satellite Application Facility on Atmospheric Composition Monitoring (AC SAF) project, covering the period 2007-2016. Comparison of GOME-2A total ozone with ground observations shows mean differences of about - 0.7 ± 1.4 <svg:svg xmlns:svgCombining double low linehttp://www.w3.org/2000/svg widthCombining double low line52pt heightCombining double low line10pt classCombining double low linesvg-formula dspmathCombining double low linemathimg md5hashCombining double low linedba8c66e297c0601baccc6ab115a0086><svg:image xmlns:xlinkCombining double low linehttp://www.w3.org/1999/xlink xlink:hrefCombining double low lineamt-12-987-2019-ie00001.svg widthCombining double low line52pt heightCombining double low line10pt srcCombining double low lineamt-12-987-2019-ie00001.png/></svg:svg> % in the tropics (0-30 ĝ ), about + 0.1 ± 2.1 <svg:svg xmlns:svgCombining double low linehttp://www.w3.org/2000/svg widthCombining double low line52pt heightCombining double low line10pt classCombining double low linesvg-formula dspmathCombining double low linemathimg md5hashCombining double low line63d75ddfa7d430e7ceb7a4033cb0075f><svg:image xmlns:xlinkCombining double low linehttp://www.w3.org/1999/xlink xlink:hrefCombining double low lineamt-12-987-2019-ie00002.svg widthCombining double low line52pt heightCombining double low line10pt srcCombining double low ...